A different interpretation from outside the network. Issue 3 (1st September 2016) - Powell, Martin
ABSTRACT: This review provides a critique of 'Democratic Governance' by one of the leading commentators on governance, Mark Bevir, focusing on the UK New Labour government and public services. It examines three main issues. First, an 'internal' critique exploring what this text adds to Bevir's earlier contributions on governance finds that it focuses on 'early' New Labour. Second, the 'story' presented here is rather different to Bevir's, focusing on markets and hierarchies rather than networks. Third, the review argues that some of the data and methods used by Bevir in his interpretative, decentred approach may not give as 'thick' a description as he claims.